Effect of cholesterol-poly(N,N-dimethylaminoethyl methacrylate) on the properties of stimuli-responsive polymer liposome complexes - Alves, P. (2013)
The development of new polymer–liposome complexes (PLCs) as delivery systems is the key issue of this work. Three main areas are dealt with: polymer synthesis/characterization, liposome formulation/characterization and evaluation of the PLCs uptake by eukaryotic cells. Poly(N,N-dimethylaminoethyl methacrylate) (PDMAEMA) with low molecular weight and narrow polydispersity was synthesized by Atom Transfer Radical Polymerization (ATRP). The polymers were synthesized using two different bromide initiators (cholesteryl-2-bromoisobutyrate and ethyl 2-bromoisobutyrate) as a route to afford PDMAEMA and CHO-PDMAEMA. Both synthesized polymers (PDMAEMA and CHO-PDMAEMA) were incorporated in the preparation of lecithin liposomes (LEC) to obtain PLCs. Three polymer/lipid ratios were investigated: 5, 10 and 20%. Physicochemical characterization of PLCs was carried out by determining the zeta potential, particle size distribution, and the release of fluorescent dyes (carboxyfluorescein CF and calcein) at different temperatures and pHs. The leakage experiments showed that CHO covalently bound to PDMAEMA strongly stabilizes PLCs. The incorporation of 5% CHO-PDMAEMA to LEC (LEC_CHO-PD5) appeared to be the stablest preparation at pH 7.0 and at 37 °C. LEC_CHO-PD5 destabilized upon slight changes in pH and temperature, supporting the potential use of CHO-PDMAEMA incorporated to lecithin liposomes (LEC_CHO-PDs) as stimuli-responsive systems. In vitro studies on Raw 264.7 and Caco-2/TC7 cells demonstrated an efficient incorporation of PLCs into the cells. No toxicity of the prepared PLCs was observed according to 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. These results substantiate the efficiency of CHO-PDMAEMA incorporated onto LEC to assist for the release of the liposome content in mildly acidic environments, like those found in early endosomes where pH is slightly lower than the physiologic. In summary, the main achievements of this work are: (a) novel synthesis of CHO-PDMAEMA by ATRP, (b) stabilization of LEC by incorporation of CHO-PDMAEMA at neutral pH and destabilization upon slight changes of pH, (c) efficient uptake of LEC_CHO-PDs by phagocytic and non-phagocytic eukaryotic cells.